PERAN BRAND AWARENESS SEBAGAI VARIABEL INTERVENING DALAM PENGARUH IKLAN DAN ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK MAKE OVER (Studi Kasus Pada Make Up Artis di Solo) - Ningrum, Retno (Universitas Of Surakarta, 2020)
AbstractOne of the factor that influence of brand awareness is the promotion of strategy, advertising on television becomes the choice in conventional promotion. The rapid development of technology is very influential in the promotion espectially social media through social endorser service is the right choice.The purpose of forming brand awareness is to provide a number competitive advantages, brand awarness is considered capable of driving on puchasing decisions.This study aims to determine the direct and indirect effects of advertising and endorsers on the formation of brand awarness representing intervening variable in the decisions purchase cosmetic product of Make Over.The population is make up artist in Solo. The result is advertising and endorser, it’s significantly proven influencing of brand awarness. Brand awareness significanly mediate advertesing to purchasing decision (indirect effect), but not significanly mediate endorser to to purchasing decision.